Delisting Sukarela : Analisis Kuantitatif Atas Kinerja Saham dan Arus Kas Sebelum Keluar dari Pasar - Annisah Febriana; Gusti Dian Prayogi (BADAN PENERBIT STIEPARI PRESS, 2025)
Voluntary delisting is a process in which a company listed on the stock exchange voluntarily decides to remove its shares from the exchange. According to data from the Indonesia Stock Exchange (BEI), between 2013 and 2023, 65 companies have delisted, with approximately 40% of them opting for voluntary delisting. This increase indicates that voluntary delisting is becoming a more common phenomenon and a strategic consideration for companies. The urgency of this study is closely related to investor protection, market stability, and improving corporate governance. This research is also aligned with the Sustainable Development Goals (SDGs) Goal 8, which emphasizes decent work and economic growth, particularly the importance of expanding access to financial services and strengthening national financial institutions, including the capital market. This study uses a quantitative approach with secondary data, covering the observation period from 2013 to 2023. The analytical technique used is Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The findings show that stock performance and cash flow from operational activities significantly influence the likelihood of a company opting for voluntary delisting, both partially and simultaneously. The study’s findings emphasize that voluntary delisting is not solely driven by regulatory factors, but is a combination of the company’s internal conditions, such as healthy cash flow, market signals reflected in stock prices, and ownership strategy. Therefore, companies may choose voluntary delisting as part of a strategy to achieve specific goals, such as improving efficiency, restructuring the business, or reducing the costs associated with maintaining a public listing. This study provides valuable insights into the factors influencing a company’s decision to pursue voluntary delisting.